U-PB SYSTEMATICS OF THE MCCLURE MOUNTAIN SYENITE: THERMOCHRONOLOGICAL CONSTRAINTS ON THE AGE OF THE 40AR/39AR STANDARD MMHB - Schoene B.; Bowring S.A. (My University, 2006)
Recent advances in U-Pb geochronology allow unprecedented levels of precision in the determination of geological ages. However, increased precision has also illuminated the importance of understanding subtle sources of open-system behavior such as Pb-loss, inheritance, intermediate daughter product disequilibria, and the accuracy of the model assumptions for initial Pb. Deconvolution of these effects allows a much richer understanding of the power and limitations of U-Pb geochronology and thermochronology. In this study, we report high-precision ID-TIMS U-Pb data from zircon, baddelleyite, titanite and apatite from the McClure Mountain syenite, from which the 40Ar/39Ar hornblende standard MMhb is derived. We find that excess 206Pb in zircon due to inclusions of high-Th minerals and elevated Th/U in titanite and apatite jeopardize the utility of the 238U-206Pb system in this rock. Strongly air-abraded zircons give dates that are younger than chemical-abraded zircons, which yield a statistically robust 207Pb/235U date of 523.98± 0.12 Ma that is interpreted as the crystallization age. We explore the best method of Pbc correction in titanite and apatite by analyzing the U-Pb isotopes of K-feldspar and using 2-D and 3-D regression methods-the latter of which yields the best results in each case. However, the calculated compositions of Pbc for titanite, apatite and K-feldspar are different, implying that using a single Pbc correction for multiple U-Pb thermochronometers may be inaccurate. The U-Pb thermochronological results are used to predict a closure time for Ar in hornblende of 522.98±1.00 Ma. Widely cited K-Ar and 40Ar/39Ar dates overlap with the U-Pb date, and relatively large errors make it impossible to verify whether U-Pb dates are systematically ≥ 1% older than K-Ar and 40Ar/39Ar dates. © Springer-Verlag 2006.